2009
DOI: 10.1007/s10753-009-9166-7
|View full text |Cite
|
Sign up to set email alerts
|

Schisantherin A Exhibits Anti-inflammatory Properties by Down-Regulating NF-κB and MAPK Signaling Pathways in Lipopolysaccharide-Treated RAW 264.7 Cells

Abstract: Schisantherin A, a dibenzocyclooctadiene lignan isolated from the fruit of Schisandra sphenanthera, has been used as an antitussive, tonic, and sedative agent under the name of Wuweizi in Chinese traditional medicine. In the present study, we carry out a screening program to identify the anti-inflammatory potentials of schisantherin A. We found that schisantherin A reduced lipopolysaccharide (LPS (1 mg/L))-induced levels of TNF-alpha, IL-6, NO, and PGE2 (p<0.01 or p<0.05), and also reduced levels of iNOS and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 36 publications
6
56
0
Order By: Relevance
“…The EtOAc layer was repeatedly subjected to column chromatography on silica gel, Sephadex LH-20, and RP-18 to afford a new lignan, namely schisandrin A1 (1), together with 9 known ones. These known compounds were identified as schisantherin A (2) [12] (also known as gomisin C or wuweizi ester A) [14], wuweizisu C (3) [15], gomisin J (4) [16], schizandrin (5) [17], schisanbicolorin A (6) [18], (þ)-1-hydroxypinoresinol (7) [19], 8,8 0 -dihydroxypinoresinol (8) [20], clemaphenol A (9) [21], and (þ)-anwuligan (10) [22] (Fig. 1) by comparison with reported spectroscopic data.…”
Section: Isolation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The EtOAc layer was repeatedly subjected to column chromatography on silica gel, Sephadex LH-20, and RP-18 to afford a new lignan, namely schisandrin A1 (1), together with 9 known ones. These known compounds were identified as schisantherin A (2) [12] (also known as gomisin C or wuweizi ester A) [14], wuweizisu C (3) [15], gomisin J (4) [16], schizandrin (5) [17], schisanbicolorin A (6) [18], (þ)-1-hydroxypinoresinol (7) [19], 8,8 0 -dihydroxypinoresinol (8) [20], clemaphenol A (9) [21], and (þ)-anwuligan (10) [22] (Fig. 1) by comparison with reported spectroscopic data.…”
Section: Isolation and Characterizationmentioning
confidence: 99%
“…Recent pharmacological studies have revealed that these compounds accounted for anti-oxidant [2,3], anti-HIV [4,5], antihepatitis B virus [6], and anti-proliferative multiple bio-effects [7]. In addition, schisantherin A (2) has been reported to exhibit anti-inflammatory properties by down-regulating NF-kappaB and MAPK signaling pathways in lipopolysaccharide-treated RAW 264.7 cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…68 LPS triggers the translocation of NF-B leading to the expression of NF-B-regulated genes, including TNF-, IL-6, COX-2 and iNOS, in murine macrophage RAW 264.7 cells. 69 These results demonstrated that betaine treatment inhibited the LPS-induced expression of TNF-, IL-6, COX-2 and iNOS in RAW 264.7 cells. 65 These results suggest that betaine might be a candidate for a potential anti-inflammatory or cancer chemopreventive agent.…”
Section: Modulation Of Colitis-associated Colon Tumorigenesismentioning
confidence: 75%
“…The inhibition of the production of these inflammatory mediators is an important target in the treatment of inflammatory diseases. Hence, LPS-induced macrophages have usually been used as a model for evaluating the anti-inflammatory effects of various agents [12,13].…”
Section: Discussionmentioning
confidence: 99%